Alt -Coin: An Energy Coin to Empower the Future (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An authenticated peer-to-peer version of e-cash would allow online transactions to be sent directly from sender to receiver without going through any financial institution. Alt- Coin is a digital currency that unlike traditional currencies, do not rely on a centralized authority.  Instead, Alt-Coin is based on a community of volunteers that collectively implement a replicated ledger and verify transactions. Digital signatures give us a part of the acknowledgement, but the main benefits are gone if a responsible third party is still needed to prevent multiple- spending. While transactions are conducted between people, bit coin can’t give solid privacy guarantees: any transactions are being recorded in a decentralized public ledger, from which far more information can be abstracted. But Alt-Coin doesn’t tackle some of these privacy issues by unlinking transactions from the payment’s origin like zero coins do. It shows transaction destinations details and given amounts just like bit coin, and has the same functionality as of bit coin. In Block chain, people performing Forks could be ignored as they are indicative of unpredictability among the copies in the network.  We then show what may be accomplished by pushing the modern-day protocol to its restriction with unilateral modifications to the customer’s behavior. The network timestamps affair by hashing them into an in-progress chain of hash-based verification-of- work, forming a  record that can’t be changed without doing it again the verification-of-work. The longest chain not only shows as verification of the order of events being watched but proof that it came from the largest pool of CPU power. Many Alt-Coin has achieved only scant consumer transaction volume, with an average well below one daily transaction for the few merchants who accept it. Its volatility is significantly higher than the volatilizes of widely used currencies, imposing considerable short- term risk upon users. We then show what can be obtained by pushing the current rules to its limit with unilateral changes to customer behavior. We then display what can be completed with the aid of promoting the current protocol to its restriction with unilateral changes to the purchaser’s behavior. In this paper, we will get a top-level view of ways alt-coin can be fork form bit coin.